Analisis Penerapan Sistem Informasi Akuntansi Pelaporan Keuangan terhadap Perkembangan Usaha Mikro Mentainity - Brigitta, Gabriella; Maratno, Sylvia Fettry Elvira (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2025)
This study focuses on analyzing the implementation of financial record-keeping in Mentainity, a micro culinary enterprise, and its contribution to business development. The purpose of this research is to understand how financial recording is carried out and to what extent it supports business management and decision-making. Mentainity is managed by two people and still applies a manual recording system using Microsoft Excel without utilizing accounting applications. This research employs a qualitative descriptive method with data collection techniques including in-depth interviews, participatory observation, documentation, and literature study. Data validity was ensured through triangulation techniques. The findings indicate that although the financial recording system is still simple, it provides significant benefits to the business owners. Manual recording helps evaluate business performance, estimate production needs, and support more rational business decisions. Routine recording also raises awareness of financial conditions, particularly regarding cash flow and profitability. However, several challenges remain, such as limited accounting knowledge, lack of human resources, and the absence of integration between inventory records and financial reports. These constraints prevent financial information from fully reflecting the overall condition of the enterprise. In conclusion, even a simple financial recording system plays a positive role in managing micro businesses. This study recommends improving financial literacy and adopting appropriate technology solutions tailored to micro-scale enterprises in order to strengthen financial management and support business development for Mentainity.